Cross-species high-resolution transcriptome profiling suggests biomarkers and therapeutic targets for ulcerative colitis - Yarani, Reza; Palasca, Oana; Doncheva, Nadezhda T.; Anthon, Christian; Pilecki, Bartosz; Svane, Cecilie A. S.; Mirza, Aashiq H.; Litman, Thomas; Holmskov, Uffe; Bang-Berthelsen, Claus H.; Vilien, Mogens; Jensen, Lars J.; et al. (Frontiers in Molecular Biosciences, 2023)
Background Ulcerative colitis (UC) is a disorder with unknown etiology, and animal models play an essential role in studying its molecular pathophysiology. Here, we aim to identify common conserved pathological UC-related gene expression signatures between humans and mice that can be used as treatment targets and/or biomarker candidates. Methods To identify differentially regulated protein-coding genes and non-coding RNAs, we sequenced total RNA from the colon and blood of the most widely used dextran sodium sulfate UC mouse. By combining this with public human UC data, we investigated conserved gene expression signatures and pathways/biological processes through which these genes may contribute to disease development/progression. Results Cross-species integration of human and mouse UC data resulted in the identification of 1442 genes that were significantly differentially regulated in the same direction in the colon and 157 in blood. Of these, 51 genes showed consistent differential regulation in the colon and blood. Less known genes with importance in disease pathogenesis, including SPI1, FPR2, TYROBP, CKAP4, MCEMP1, ADGRG3, SLC11A1, and SELPLG, were identified through network centrality ranking and validated in independent human and mouse cohorts. Conclusions The identified UC conserved transcriptional signatures aid in the disease phenotyping and future treatment decisions, drug discovery, and clinical trial design.